A Comparative Analysis of Conceptual Bases of Modern Educational Systems and Educational Practices (on the Example of Comparison of the System of Developmental Instruction and Reflective-Activity Approach) - Zaretsky V.K.; Zaretsky Yu.V.; Ostroverkh O.S.; Tikhomirova A.V.; Fedorenko E.Y. (Психолого-педагогические исследования)
he article is written in the framework of the research project of the Moscow state university of psychology and education "Development of a conceptual model of a new school". In this article, the authors attempt to start a comparative analysis of conceptual educational systems and practices that have common value and theoretical and methodological foundations and can become the basis for building the educational process within the framework of the project being developed. It is important to enrich understanding of how the principles of subjectness, cooperation, and development can be implemented on a school-wide scale through a comparison of the system of developmental instruction training and the reflexive-activity approach. The article attempts to integrate these approaches in the process of designing a new school.